Membangun Karakter Anak Usia Dini Di Era Digital: Relevansi Kontekstual Pemikiran Al-Ghazali - M Fathurahman; Basuki (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to analyze the relevance of Al-Ghazali's thoughts in Ihya' Ulum al-Din to the character formation of children in the digital era. The background of this research is based on the phenomenon of moral degradation, as well as the dominance of cognitive aspects in modern education, which pays little attention to spiritual and ethical dimensions. The research method is qualitative with library research, through critical analysis, interpretation, and synthesis of primary and supporting literature. The results show that Al-Ghazali's concept of character education centers on the development of the soul (tazkiyat al-nafs), moral habituation (riyadhah), self-control, and the role model of educators. Character is understood as an inner disposition formed through the continuous internalization of values. In the context of the digital era, these values ​​are relevant for strengthening self-awareness (muraqabah), forming positive habits in the use of technology, and highlighting the significant role of teachers and parents as moral role models. This study concludes that Al-Ghazali's thoughts have a substantive contribution to developing a holistic and adaptive model of character education to technological developments.